Oral hygiene practices and associated factors among primary school children in Alzintan City, Libya - Trabelsi, Naeima Ahmed (2016)
Introduction: Preservation of good oral hygiene in children is important for the development of strong, healthy teeth and to decrease the possibility of dental caries. Objective: The objective of the study is to determine oral hygiene practices and its associated factors among primary school children aged 9-12 years old in Al Zintan City, Libya. Methodology: A cross sectional observational study design was used in this study among primary school children in Al Zintan City, Libya. Stratified sampling within 29 schools provided a random sample of 691 schoolchildren. Information about oral hygiene practices among school children was collected through a self-constructed questionnaire survey. Data that were collected was analyzed by using Statistical Package of Social sciences (SPSS) for version 22 software. There were three steps of analyzing data, namely univariate, bivariate, and multivariate data analysis. Results: From the results, there was 53.7% (n = 371) of respondents had proper practices on oral hygiene, and 46.3% (n = 320) of respondents have improper practices on oral hygiene. There was no statistically association between oral hygiene practices and different age groups of respondents (P = 0.57). However, there was significant association between oral hygiene practices and gender, level of mother education, level of father education and role of parents in oral health care of their children (P < 0.05). Bivariate analysis revealed no statistically significant association regarding oral hygiene practices between children with high and low knowledge (P = 0.361). In addition, oral hygiene practices are not significantly associated with dental history of respondents (P = 0.21). However, There was significant association between oral hygiene practices and dietary habits of respondents (P = 0.01) and also there was significance association between oral hygiene practices and attitude toward oral hygiene among primary school children of Al Zintan city, Libya (P = 0.009). Conclusion: It is concluded that, the prevalence of oral hygiene practices among 9- 12 years-old school children in Al Zintan City, Libya is not satisfactory. The participants had improper oral health practices, insufficient knowledge, incorrect attitude and practice regarding oral health. It is recommended that children and parents’ awareness about oral hygiene practices should be increased.